Prediction of fatal cardiovascular events in patients with newly diagnosed non-small cell lung cancer - A. A. Filippov; N. G. Lozhkina; E. I. Shefer; P. S. Ruzankin; M. I. Voevoda (Российский кардиологический журнал)
Aim. To study risk factors for fatal cardiovascular events in patients with non-small cell lung cancer over two years of standard treatment.Material and methods. This pilot retrospective non-randomized cohort study included 179 patients who were consecutively admitted to the chemotherapy department of City Clinical Hospital 1 from January to December 2020 with a confirmed diagnosis of non-small cell lung cancer based on the comprehensive examination and morphological verification according to the 2018 clinical guidelines on bronchial and lung cancer. Diagnosis and treatment of cardiovascular diseases were carried out according to national clinical guidelines. The follow-up period for non-small cell lung cancer and cardiovascular disease was 2 years. Logistic regression models were considered to assess the risk of cardiovascular death. The model accuracy was assessed by a cross-validation.Results. The best model in terms of the sensitivity and specificity sum according to a cross-validation was the model with the following explanatory variables: sex, cancer stage, platinum-based chemotherapy, etoposide, immunotherapy, surgical treatment. This model showed a sensitivity of 70,1% and a specificity of 82,1%.Conclusion. This approach is easy to implement and may optimize treatment for patients with non-small cell lung cancer.